(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It was the challenge beforepost-independence India to consolidate and preserve the new form of societythat still was in the grip of poverty, ignorance and backwardness. People hadto work hard to make India free of all these evils. However, those who tookparticipation in the movement for freedom, not an insignificant number, thoughat the lower cadre, belonged to India’s villages. The problem that Markandayahas taken is—the struggle between urban and non-urban elements of life, betweenpre and post independence, between old and new, between traditional eastern andmodern western ways.